CLINICAL SIGNIFICANCE OF INTRALUMINAL ENDOSCOPY IN DIAGNOSTICS OF DIGESTIVE TRACT DISEASES IN CHILDREN - M.M. Lokhmatov; P.L. Shcherbakov ("Paediatrician" Publishers LLC, 2008)
The article presents the authors' data on the information value of different methods of endocsopic examination of gastrointestinal tract in children. Examination data of 2098 children with different pathologies of digestive organs and 96 children from control group, are given. The examination algorithm of children suffering from digestive tract diseases with the use of the latest methods of intraluminal endoscopy, is formulated. Key words: children, endoscopy, gastrointestinal tract, diagnostics.